Intellectual freedom manual - American Library Association. Office for Intellectual Freedom (Chicago : American Library Association, 2010)
Updated for the first time since 2005, this indispensable volume includes revised interpretations of the Library Bill of Rights along with key intellectual freedom guidelines and policies.
Part I. Intellectual Freedom and Libraries: an overview. Intellectual freedom: an enduring and all-embracing concept / Candace D. Morgan -- ALA and intellectual freedom: a historical overview / Judith F. Krug and Candace D. Morgan -- Challenges and issues today / Candace D. Morgan -- Part II. Library Bill of Rights: Library Bill of Rights: policy statement -- Library Bill of Rights: interpretations -- Part III. Protecting the Freedom to Read: The freedom to read -- Libraries: an American value -- Policies and statements related to access to information, library resources, and library services -- Policies and statements related to confidentiality, privacy, and governmental intimidation -- Part IV. Code of Ethics of the American Library Association: Code of ethics of the American Library Association -- Enforcement of the "Code of Ethics of the American Library Association": questions and answers -- Resolutions on workplace speech -- Questions and answers on speech in the workplace: an explanatory statement of the "ALA Code of Ethics" -- Part V. Intellectual Freedom and the Law: Public libraries and the public forum doctrine / Theresa Chmara -- Minors' First Amendment rights to access information / Theresa Chmara -- Privacy and confidentiality in libraries / Deborah Caldwell-Stone -- Part VI. Preserving, Protecting, and Working for Intellectual Freedom: Preparing for and responding to challenges / Beverley Becker -- Communicating the intellectual freedom message / Larra Clark with Macey Morales -- Lobbying for intellectual freedom / ALA Washington Office -- Rallying for intellectual freedom: where to go for help and how you can help / Angela Maycock and Nanette Perez.
Includes bibliographical references (pages 419-421) and index.
Keywords: Libraries -- Censorship -- United States -- Handbooks, manuals, etc; Intellectual freedom -- United States -- Handbooks, manuals, etc; Intellectual freedom; Libraries -- Censorship; United States; Libraries -- Censorship -- United States -- Handbooks, manuals, etc; Handbooks and manuals; Handbooks and manuals